2016
DOI: 10.1007/s00330-015-4192-3
|View full text |Cite|
|
Sign up to set email alerts
|

Performance of ultralow-dose CT with iterative reconstruction in lung cancer screening: limiting radiation exposure to the equivalent of conventional chest X-ray imaging

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 40 publications
(37 reference statements)
1
37
0
Order By: Relevance
“…However, the edge spreading in the MBIR images was inferior compared to the FBP and ASIR images in air plugs (simulating cavity-like metastases, small cysts, or centrilobular emphysemas) vs lung tissue boundaries. This observation may support previous findings of inferior detection of small ground-glass nodules in the lungs with MBIR (17,30,31). Furthermore, the regularization in MBIR may result in highly nonstationary noise in the images, specifically at the contrast edges (34).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the edge spreading in the MBIR images was inferior compared to the FBP and ASIR images in air plugs (simulating cavity-like metastases, small cysts, or centrilobular emphysemas) vs lung tissue boundaries. This observation may support previous findings of inferior detection of small ground-glass nodules in the lungs with MBIR (17,30,31). Furthermore, the regularization in MBIR may result in highly nonstationary noise in the images, specifically at the contrast edges (34).…”
Section: Discussionsupporting
confidence: 88%
“…However, for characterizing ground-glass opacities and emphysemas, LD levels are clearly inferior to standard-dose levels. Similarly, Huber et al (30) reported a drop of sensitivity for the detection of small (5 mm) groundglass nodules. According to their results, however, the smallest ground-glass nodules were still better visualized than the comparatively sized solid nodules.…”
Section: Discussionmentioning
confidence: 89%
“…It is important to be aware that in pursuit of low dose, one must not compromise on diagnostic quality. Recent study in chest phantom examining detectability of lung nodule at chest radiograph equivalent dose has shown overall detection rates of 93.3% with DLP: 9 mGy cm [25]. Their detection rates for small 5 mm solid nodules were 83.9% using iterative reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Ultralow-dose CT, which limits radiation exposure to the equivalent of chest X-rays in two planes, has shown promise for lung cancer screening 72 , so this may change should further studies demonstrate benefits for this technique in the follow-up of bone sarcoma.…”
Section: Advances In Follow-upmentioning
confidence: 99%